Evaluation of patella alta using MRI measurements in adolescents - Baris Yilmaz; Guzelali Ozdemir; Evrim Sirin; Esin D Cicek; Burcu S Anıl; Goncagul Bulbun (Indian Journal of Radiology and Imaging, 2017)
Purpose: To determine whether or not there were any differences in the measurement techniques used by orthopedic and radiology specialists in the evaluation of magnetic resonance (MR) images for the diagnosis of patella alta in adolescents. Materials and Methods: Evaluations were performed by three orthopedic specialists (Group I) and three radiology specialists (Group II) regarding the presence of patella alta in 40 adolescents cases using the Insall–Salvati, Caton–Deschamps, Blackburne–Peel, and modified Insall–Salvati indices on MR images obtained to diagnose patellar instability. Results: The Fleiss Kappa conformity levels for Insall–Salvati, Caton–Deschamps, Blackburne–Peel, and modified Insall–Salvati measurements were 0.531, 0.559, 0.246, and 0.272, respectively, in Group I, and 0.699, 0.346, 0.516, and 0.394, respectively, in Group II. Conclusion: The radiology specialists were found to have greater conformity in the evaluation of all patella alta indices, which was probably due to their greater familiarity with radiological measurements than that of the orthopedic specialists.